Changing One's First Name in France: A Fountain of Youth?. (September 2014) - Coulmont, Baptiste
Abstract : A change of name is a change of identity. Many studies have focused on changes in ethnic identity, because those who change their name are often descendants of migrants or migrants themselves. This article focuses on first name changes in France. It shows that those who change their first name are indeed overwhelmingly the descendants of migrants, but that their identity change is multidimensional. Changing one's first name is also a way to get a younger first name.